ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN PRODUK MAKANAN DAN MINUMAN HALAL DI JAKARTA - Nawawi, Muhammad Tony (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2018)
This study aims to determine the effect of variables attitude, subjective norm, perceived behavioral control, and intentions of the decision to buy cosmetic products are safe and lawful to the Moslem in University Tarumanagara. The analysis used the two-track analysis using SPSS program. The analysis is divided into two: first the decision to buy cosmetic products are safe and the decision to buy a halal cosmetics. The results of this study is expected to be beneficial for consumers to pay more attention to safety and halal cosmetic products to be purchased. The government is expected to explicitly require the employer to provide information security and halal cosmetic products, due to the legality and certification of halal products will provide protection and ease of purchasing products cosmetic. For Moslem businessman in the presence of security guarantees and halal products, it is hoped will be improve competitiveness and sales.